Ut in his reperias aliquam partem uasorum Dei: Jerome and the Pagan Culture in the CDan - Daniela Scardia (Religions)
The image of the vasa domus Dei, repeated on two occasions in the book of the prophet Daniel (Dan 1:2 and 5:4), enables Jerome to formulate an explicit judgement on pagan culture. Drawing extensively on a well-established repertoire, he highlights in one case its positive aspects and in the other its negative ones, and so in CDan 1,1,2b, he underlines the presence, at least in philosophy, of some truths drawn from the doctrine of God; in CDan 2,5,4, he discusses the wicked use the heretics make of the saeculares litterae.